Religious and Philosophical Conversion in the Ancient Mediterranean Traditions - Löhr, Hermut; Despotis, Athanasios (Ancient Philosophy & Religion, 2022)
The interest in interdisciplinary research on the experience of religious conversion or spiritual transformation grows progressively. In light of this burgeoning area of study, this volume explores conversion or converting experience in the ancient Mediterranean with attention to early Judaism, early Christianity, and philosophy in the Roman empire. The contributions include both historical and philological reconstructions relying on source material and utilizing interdisciplinary approaches. Similarly, the authors analyze the literary use of the motif of conversion, the topic of philosophical conversion as well as ritual, social and embodied aspects of spiritual transformation.